The Influence of Transformational Leadership on Task Performance and Organizational Citizenship Behaviors: The Mediation Role of Work Engagement and Organizational Identification (Case Study on the Secretariat General of the Ministry of Finance of the Rep - Yusuf Aji Darmawan; Elok Savitri Pusparini; Imbuh Sulistyarini; Ayu Aprilianti (Indonesian Interdisciplinary Journal of Sharia Economics (IIJSE), 2026)
This study aims to determine the direct influence of transformational leadership on task performance and organizational citizenship behaviors and through the mediation role of work engagement and organizational identification. Data were collected through questionnaires and analyzed using Structural Equation Modeling. A total of 367 employees of the Ministry of Finance Secretariat General participated as research samples. The results of this study indicate that transformational leadership has an indirect effect on organizational citizenship behaviors through work engagement and organizational identification, and on task performance through work engagement although only partial mediation. However, transformational leadership does not have an indirect effect on task performance through organizational identification, so that organizational identification does not mediate the effect of transformational leadership on task performance. This study also shows that transformational leadership has a direct influence on task performance and organizational citizenship behaviors of employees of the Ministry of Finance Secretariat General, especially related to concern for the image of the organization. Therefore, organizations need to encourage technical-level leaders (echelon IV) to always demonstrate the characteristics of a transformational leader so that employees below them are increasingly motivated to defend the agency when other agencies criticize it, show pride when representing the agency in public, and express loyalty to the organization.